Risk Factors for the Incident of Gingivitis in Patients at Cera Dental Care Clinic Bogor City in 2024 - Damaiyanti, Mamay; Maritasari, Dwi Yulia; Anita, Fitri (Universitas Ibn Khaldun Bogor, 2025)
Gingivitis disease in Indonesia reached 829,573 cases based on the 2023 Indonesian Health Survey. Secondary causes include local factors such as carious cavities, failed restorations, food debris, poorly designed dentures, orthodontic devices and irregular tooth arrangement. at the Cera Dental Care Clinic in Bogor City, in mid-2024, out of a total of 105 patients, the number of gingivitis patients was 75 patients (28.57%). The purpose of this study was to determine the risk factors for gingivitis in patients at the Cera Dental Care Clinic in Bogor City in 2024. This type of research is quantitative, with a cross-sectional approach. The sample of this study was adult patients who visited Cera Dental Care Kota for treatment totaling 102 respondents. The sampling technique used purposive sampling. Data collection used observation sheets, data analysis used the chi square test. The results of the study showed the frequency distribution of gingivitis in patients with the largest number experiencing gingivitis, totaling 58 respondents (56.9%). There was a relationship between piles of food scraps (P Value 0.019), use of orthodontic appliances (P Value 0.008, OR 4.2) and irregular tooth arrangement (P Value 0.029, OR 2.8) and the incidence of gingivitis in patients at the Cera Dental Care Clinic in Bogor City in 2024. It is recommended to carry out health promotion in dental health facilities in handling gingivitis problems, such as providing education on how to carry out oral dental care for users of orthodontic appliances.